2015
DOI: 10.1002/jhet.2460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anti‐Microbial, and Cytotoxic Activities Evaluation of Some New Pyrido[2,3‐d]Pyrimidines

Abstract: Novel pyridine derivatives 1d and 7, pyrido[2,3‐d]pyrimidine derivatives 2a, 2b, 2c, 2d, 3a, 3b, 3c, 3d, 4a, 4b, 4c, 4d, 5a, 5b, 5c, 5d, 6a, 6b, 6c, 6d, 8a,8b, and 9a,9b were synthesized and screened for their anti‐microbial and cytotoxic activities. Compounds 2b, 2c, 3b, 3c, 5b, 5c, 6b, 6c, and 7 showed excellent anti‐microbial activities against all the tested bacteria and fungi compared to the reference drugs. Furthermore, they exhibited high safety profile in cytotoxicity test except 2c and 3c. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Continuing our interest in preparing of new heterocyclic compounds and examining their various biological activities [ 1 6 ], this work was designed to prepare new derivatives of condensed and non-condensed five-membered rings with pyrimidine. Pyrimidine derivatives have aroused the interest of researchers in recent years, as they have demonstrated a wide variety of biological activities such as antibacterial [ 6 ], antiallergic, antihypertensive [ 7 ] and antitumor activity [ 5 , 8 ], along with their cardiopulmonary and bronchodilating effect [ 9 ]. It has been observed that the substitution of the benzene ring in pyrimidine derivatives with heterocyclic moieties such as pyrrole and thiophene shows some biological activities such as anti-proliferative and anti-inflammatory activities [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our interest in preparing of new heterocyclic compounds and examining their various biological activities [ 1 6 ], this work was designed to prepare new derivatives of condensed and non-condensed five-membered rings with pyrimidine. Pyrimidine derivatives have aroused the interest of researchers in recent years, as they have demonstrated a wide variety of biological activities such as antibacterial [ 6 ], antiallergic, antihypertensive [ 7 ] and antitumor activity [ 5 , 8 ], along with their cardiopulmonary and bronchodilating effect [ 9 ]. It has been observed that the substitution of the benzene ring in pyrimidine derivatives with heterocyclic moieties such as pyrrole and thiophene shows some biological activities such as anti-proliferative and anti-inflammatory activities [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potential anticancer activity was observed by all the synthesized compounds. pyrimidine nucleus as a pharmacologically potential scaffold, including antitumor properties [36]. They also reported that organic molecule bearing fluorine [37] or trifluoromethyl [38] group at a strategic position leads to dramatic changes in the properties and activities of the molecule.…”
Section: Ethyl 2-cyanoacetate As Precursormentioning
confidence: 99%
“… 1 , 2 Also, [1,2,4]triazole derivatives have been reported as antimicrobial, insecticidal, fungicidal, antidepressant, hypnotic, anti-inflammatory, antihypertensive, and plant growth regulator. 3 − 8 On the other hand, 1,3,4-oxadiazole has become an essential building unit for the creation of new drugs where a literature survey showed that a slight systemic change in 1,3,4-oxadiazole moiety structure could lead to qualitative as well as quantitative changes in 1,3,4-oxadiazole derivative activity, which convinced us to start synthesizing different new 1,3,4-oxadiazole derivatives in order to increase their activity and lower their toxicity. Over the last 2 decades, the synthesis of novel 1,3,4-oxadiazole derivatives and the investigation into their chemical properties and biological behavior have increased.…”
Section: Introductionmentioning
confidence: 99%